The Implementation of the Independent Learning Curriculum in Indonesian Language Instruction to Foster Student Creativity - Maulita Hasibuan, Riska; Kusmana, Ade; Rustam, Rustam (STAI Miftahul Ula Nganjuk, 2024)
This study aims to examine, describe, and analyze the implementation of the